ANALYSIS OF THE INFLUENCE OF DIGITAL MARKETING AND RISK PERCEPTION ON CUSTOMER DECISIONS IN USING SHARIA BANKING MOBILE APPLICATION - Frans Sudirjo; Tanti Widia Nurdiani; Joko Ariawan; Ghalib Suprianto; Andriya Risdwiyanto (Jurnal Scientia, 2023)
Mobile banking is a digital service product provided by banks to facilitate daily transactions. In Indonesia, there is sharia-based mobile banking. However, there are still many customers who have not utilized digital mobile banking services. This is partly influenced by digital marketing promotions that have not been optimal. Not only that, the increasing risk of cybercrime makes customers have a negative perception of the use of mobile banking and prefer to use an automatic teller machine. The study seeks to determine whether risk perception and digital marketing have an impact on consumers' decisions to utilize mobile banking. This study employed a quantitative methodology and gathered data from a sample of 100 participants. The normality test, multicollinearity test, heteroscedasticity test, and hypothesis test (t test, f test, and R2 test) are the data analysis procedures employed. The study's findings demonstrate a favorable relationship between perceived risk and digital marketing's ability to influence consumer choices. The results of the test for coefficient of determination yielded an R2 value of 0.75, or 75%. Customers' decisions to utilize mobile banking are influenced by digital marketing outcomes and risk perception, while the remaining percentage is explained by factors other than the independent variables employed in the study.